2016
DOI: 10.1016/j.resuscitation.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing pre- and post-shock pauses during the use of an automatic external defibrillator by two different voice prompt protocols. A randomized controlled trial of a bundle of measures

Abstract: http://www.isrctn.com unique identifier: ISRCTN72257677.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
(30 reference statements)
2
10
0
1
Order By: Relevance
“…Durch optimierte AED-Anwendung können sogar noch bessere Ergebnisse erzielt werden [ 9 ]. Das alleinige Verkürzen der Wartepausen während der Analyse, der Ladephase und der Schockanweisung ist dabei nicht ausreichend [ 1 ]. Es braucht eine ausgewogene Verbindung von klaren und präzisen Angaben mit vereinfachten Abläufen.…”
Section: Kurze Hinführung Zum Themaunclassified
“…Durch optimierte AED-Anwendung können sogar noch bessere Ergebnisse erzielt werden [ 9 ]. Das alleinige Verkürzen der Wartepausen während der Analyse, der Ladephase und der Schockanweisung ist dabei nicht ausreichend [ 1 ]. Es braucht eine ausgewogene Verbindung von klaren und präzisen Angaben mit vereinfachten Abläufen.…”
Section: Kurze Hinführung Zum Themaunclassified
“…Three RCTs [9][10][11] and 21 observational studies were identified. The evidence identified was divided into 5 categories, and results are summarized in Table 2: or between different systems that had differences in CPR fraction 3.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Although some randomized clinical trials comparing 2000 vs. 2005 CPR Guidelines showed that shortening pre-shock and post-shock CC pauses and increasing the CC fraction (CCF) did not improve survival, 18,19 more recent evidence suggests that when controlling for the effects of other resuscitation interventions, higher CCF was predictive of survival. 20 Moreover, in several other studies, it has been demonstrated that during CPR, greater CCFs were associated with higher likelihood of ROSC and survival after out-of-hospital cardiac arrests.…”
Section: Discussionmentioning
confidence: 99%